HOMONYMOUS HEMIANOPIA IN CEREBRAL INFARCTION: CASE REPORT: Poster Presentation - Case Report - Resident - Hadwer Wicaksono Pandjaitan (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Homonymous hemianopsia is a visual field defect characterized by loss of half of the visual field in each eye. Cerebral infarction in the occipital lobe is the most common cause of homonymous hemianopsia. Sudden visual field loss should be considered as a cerebral infarction for prompt management. Case Illustration : Male 43 years old, vision in both eyes appears dark on the left side since 3 months ago, complaints occur suddenly. Patients with a history of hypertension (+) hypercholesterolemia (+). Ophthalmological examination revealed visual acuity in both eyes 6/6 with normal pupillary reflexesand normal fundoscopy in both eyes. Humphrey's visual field perimetry test showed left homonymous hemianopsia. A brain CT scan examination showed multiple cerebral infarctions in the right occipital lobe, cerebellum and basal ganglia bilaterally. The patient was referred to the neurology department for further treatment. Discussion : The visual field defect pattern is used to predict the location of the lesion in the visual pathway. Neurologic symptoms that may be present in occipital lobe lesions are migraine with aura and visual hallucinations. The patient had left homonymous hemianopsia where the results of brain CT scan showed multiple cerebral infarctions in the right occipital lobe. Conclusion : Manifestations of homonymous hemianopsia can predict the presence of cerebral infarction so that in the presence of visual field defects it can be used as a predictor of intracranial abnormalities for further evaluation and collaboration with the neurology department.